Alterations in structural connectivity may contribute both to the occurrence of tics in Gilles de la Tourette syndrome and to their subsequent control. (20th January 2015) - Draper, Amelia; Jackson, Stephen R.
Abstract : This scientific commentary refers to 'Altered structural connectivity of cortico-striato-pallido-thalamic networks in Gilles de la Tourette syndrome' by Worbe et al. (doi:10.1093/brain/awu311 ).